Manajemen Pendidikan Karakter Berbasis Al-Qur’an dalam Pembentukan Akhlak Peserta Didik di Sekolah - Hanifatunnisa Hanifatunnisa; Muhammad Aditya Firdaus; Endi Suhendi (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine and analyze the planning, implementation, evaluation of Qur'an-based character education in the formation of students' morals, as well as the obstacles and solutions faced. This study uses a qualitative descriptive analysis approach and was conducted at SMK Darul Fatwa Sumedang from April to August 2021. The subjects of this study were PAI teachers, principals and BTQ teachers who were the purposive samples. Data collection techniques used in the interview, observation and documentation. Data analysis used in this research is data analysis model of Miles and Huberman, where data collection, data presentation, data reduction and conclusion are drawn. The results of the study found that character-based learning activities of theQur'an in the formation of students' morals were in accordance with the function of learning management which included planning, implementation, evaluation and all the components involved in it. The solution to minimize these obstacles is that the teacher offers additional classes outside of the BTQ and PAI subject hours, the teacher makes a list of Al-Qur'an readings for students.